Medicinal plants used to induce abortion in India-a systematic review - Sharma, Pramod Parasharam; Kature, Shilpa Kashinath; Sharma, Sakshi Promod (International Journal of Research in Medical Sciences, 2024)
Traditional practice of use of plant resources for treating various human diseases have played foremost role throughout the world. Several plants have been tested for their activity through pharmacological studies. The use of plants to induce abortion which have been practiced in different regions of India. And still today the people or communities reside in remote and distant places are mostly rely upon the plants to induce abortion. Even after a advancement in allopathic medicine, the belief still strong towards plant medicines due to its side effects. In present review 50 research publications are considered which include total 136 plants. While plant part/s used for preparation of formulations, 99 underground parts, 49 medicinal preparations made by using leaf, fruit 35, whole plant 25, bark 13, stem 11, stembark 4, flower 8 and 3 by using aerial parts. Most used method of preparation was paste, 112 formulations, which is followed by extract 59 and decoction 38. While mode of administration is concerned, 272 formulations are given orally, 25 formulations are prescribed internally and 7 for external applications.